The utilization of medicinal plants in Kolaka local community: An ethnobotanical study - Montasir, La Ode; Salzabil, Andi Zaizafun Alfianti; Rafiun, Nailah Amorita Syaqra; Kasih, Mutiara; Marsaban, Al (IAS Journal of Localities, 2023)
This research aims to find out, document, and analyze traditonal knowledge regarding plant types, processing methods, and compound contents used by the community in Kolaka District for wound healing treatments. The research method used is descriptive qualitative. The data collection techniques used observation and interviews. The results of this research show that there are 18 types of plants that are used as wound medicine in the community of Kolaka District with various methods of utilization, including grinding beans/seeds and leaves, extracting sap or essence from leaves, and using the plant stem sap, that is later applied to the injured parts of the body. The results of this research are expected to contribute academically to the field of ethnobotany, particularly concerning the utilization and developments of new medicines for various types of wounds on the body using natural ingredients, in order to anticipate dependence on chemical drugs or antibiotics which often have the potential to cause side effects. Additionally, through documenting types of plants and traditional wound treatment methods in this research, it is hoped that the preservation and originality of local knowledge regarding longstanding healthcare system within the community can be maintained.